Pengaruh Penggunaan Uang Elektronik (E-Wallet) Terhadap Perilaku Konsumtif Mahasiswa Di Kota Jambi : Studi Kasus Mahasiswa UIN STS Jambi Fakultas Ekonomi Dan Bisnis Islam Angkatan 2020-2021 - Diana Puspita Sari; Ambok Pangiuk; Nurlia Fusfita (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to determine the influence of the use of electronic money on the consumer behavior of students at UIN STS JAMBI, Faculty of Islamic Economics and Business, both partially and simultaneously. The type of data used in this research is quantitative data. Data collection was carried out by means of Questionnaires, Documentation and Interviews. The sample in this study amounted to 92 people. The data analysis used is Descriptive analysis, Variable Test, Reliability Test, Simple Linear Regression Analysis, T Test, F Test, and Coefficient of Determination Analysis. This research was carried out using simple regression analysis to determine the effect of electronic money use on consumer behavior.The results of the research explain the influence of e-wallet use on consumptive behavior among students at the Faculty of Islamic Economics and Business, UIN STS JAMBI or in other words, consumptive behavior is influenced by the use of e-wallet by 64.4%, while the remaining 35.6% is influenced by other factors. not examined in this study.